Cost‐of‐illness of melanoma in Europe – a modelling approach. (27th February 2019) - Krensel, M.; Schäfer, I.; Augustin, M.
Abstract: Background: Malignant melanoma is accounting for the vast majority of skin cancer death. The treatment and productivity loss due to morbidity or premature mortality are associated with costs for society. There are few cost‐of‐illness (COI) studies on malignant melanoma in European countries from societal perspective and currently there is no publication analysing the COI in all European countries. Objectives: The objective of the present study was to comparatively estimate COI of malignant melanoma in the European countries based on an identical approach. Methods: Cost information was obtained from results of a systematic literature research. For countries with no available cost information, a model for imputation of cost data was developed. Country‐specific costs were modelled on the national gross domestic product, health expenditures, gross national income and epidemiological data. The adjustment for purchasing power parity allowed a comparison across countries. Results: Crude national costs of malignant melanoma ranged between € 1.1 million in Iceland and € 543.8 million in Germany and resulted in € 2.7 billion for all EU/EFTA states. Estimated crude costs per patient were lowest in Bulgaria (€ 6422) and highest in Luxembourg (€ 50 734). The share of direct costs varied from 3% to 26% across countries. After adjustment for the purchasing power parity costs per patient ranged between € 14 420 in Bulgaria and € 50 961 in Cyprus. Treatment expenses and morbidity costs were markedly lower for countries that entered the EU since 2004. By contrast, mortality costs were lower in countries with a high gross domestic product per capita. Conclusion: In this first estimation, malignant melanoma induces relevant COI in Europe. There was large variation in the costs per patient due to different health care systems and expenses. Beyond decreasing patient burden, early intervention and prevention of melanoma could have a relevant potential to save costs across Europe.